Postpartum inferior vena cava thrombosis: a case report - Jagadeesan, Nithya; Kaviyarasu, Sri Vigni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Inferior vena cava thrombosis (IVCT) is an important cause of morbidity and is one of the direct causes of maternal death after delivery in developed countries. The risk of venous thromboembolism (VTE) is present throughout the pregnancy and is maximal during postpartum, especially after twin delivery. Most of the signs and symptoms of deep vein thrombosis (DVT) overlap those of normal pregnancy causing difficulty in diagnosis. We report a case of 32-year-old primigravida who developed IVCT in postoperative period following caesarean section for twin delivery at term gestation. This was diagnosed by ultrasound on evaluation for her leg pain. She was initiated on anticoagulation that was continued for a period of six months. She is on regular follow up. IVCT is rare but recognition of signs and symptoms is fundamental to start adequate therapy and avoid potential serious sequelae.